1998
DOI: 10.1046/j.1365-2354.1998.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision with community Macmillan nurses: some theoretical suppositions and case work reports

Abstract: This paper explores clinical supervision undertaken with community Macmillan Clinical Nurse Specialists in the UK. The philosophical motor is embedded in a Heideggerian existential-phenomenological framework, influenced by psychoanalytical thinking as described by Yalom. The discussion is derived from a qualitative research study designed to reach the lived-experience of five Macmillan Clinical Nurse Specialists. The author explores, in context, issues related to authenticity and project. Ideas are linked to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Clinical supervision has, for several years, been frequently used as a support for nurses in psychiatric nursing care although psychiatric nurses’ experience of clinical supervision and its effects is sparsely described in the literature. Jones (1995, 1998) stated that if clinical supervision is to become meaningful to nursing practice it requires identification of the critical elements in nursing in order to define the contribution that clinical supervision can make to each special area of nursing (e.g. psychiatric nursing).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical supervision has, for several years, been frequently used as a support for nurses in psychiatric nursing care although psychiatric nurses’ experience of clinical supervision and its effects is sparsely described in the literature. Jones (1995, 1998) stated that if clinical supervision is to become meaningful to nursing practice it requires identification of the critical elements in nursing in order to define the contribution that clinical supervision can make to each special area of nursing (e.g. psychiatric nursing).…”
Section: Introductionmentioning
confidence: 99%
“…A concept analysis of the concepts of communication and dialogue conducted by Fredriksson concludes that in nurses’ practice, the purpose of the dialogue is communication 32 . That the dialogue is important when conducting supervision is confirmed by Sloan, 26 Jones 11 and Severinsson 31 . The participants reported that creating relationships with the clients was a strategy in supervision.…”
Section: Discussion and Interpretationsmentioning
confidence: 85%
“…Literature searches indicate that there is a lack of research concerning client supervision 4 . However, supervision related to students and professionals has, to some extent, been scientifically documented 10–12 . Thus, there is a need for knowledge related to client s upervision in order to make nursing practice more scientific.…”
Section: Introductionmentioning
confidence: 99%
“…Typical sample is data from individuals, in‐group settings or literature/governmental documents. Reports that base findings on empirical sample such as observations, different types of RNs' journaling, interviews and cases have a main focus on RP as an individual process 23–42 . In contrast to reports with sample from in‐group activities such as clinical supervision, focus group discussions/interviews which have their main focus on RP as a group process, although with individual reflection (inward process) as the point of departure 43–51 .…”
Section: Resultsmentioning
confidence: 99%
“…With a critical and analytic approach, RP could facilitate awareness of nursing knowledge and practices. RNs' tacit nursing knowledge could be explained as describing nursing practice as a means to identify, review and make sense of RNs' everyday practice 30,81 . RP is judged to develop and generate creative nursing 3,67 .…”
mentioning
confidence: 99%